THE ROLE OF MEDIACULTURE IN THE PROCESS OF FORMING OF TOLERANCE IN THE GLOBAL WORLD - Ороховська, Л. А. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
The article analyzes the influence of media culture on the problem of conducting the state`s policy of multiculturalism and the problem of tolerance formation in society.